Analysis of street tree and urban infrastructure in Joubert de Carvalho Street, Maringá – Parana, Brazil - Albertin, Ricardo Massulo; Angelis, Bruno Luiz Domingos de; Silva, Frederico Fonseca; Angeoletto, Fábio Henrique Soares; Rêgo, Nicéia; Santil, Fernando (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The urban forestry on street is one aspect of urban ambience, whose importance is related to the chemical, physical, landscape, psychological, ecological, pedological, hydrological, atmospheric and acoustic funsction. But, often, the urban trees share space with urban infrastructure and can cause conflicts. The compatibility of afforestation with urban infrastructure (poles, inlets, trash cans, sidewalks) is a task that requires research, planning and management. In this context, we analyze the street tree and its relation to urban infrastructure in Joubert de Carvalho Street, in the city of Maringá, state of Paraná, South of Brazil. The methodological procedures comprised two phases: site characterization and qualyquantitative survey. The results showed that in the studied area there are 116 tree species, which 44% are species Sibipiruna (pluviosa Poincianella var. Peltophoroides (Benth) LP Queiroz) and 19% of Jacaranda (Jacaranda mimosifolia D. Don) species. 13 missing spaces of trees were identified. It was concluded that 66.00% of the trees do not cause conflicts with urban infrastructure. However, the highest levels of conflict are poles with (6.0%), buildings (8.0%) and overhead lines (11.0%).